The Influence of Inflammation on Fibrinogen Turnover and Redistribution of the Hemostatic Balance to a Prothrombotic State in High On-Treatment Platelet Reactivity-Dual Poor Responder (HTPR-DPR) Patients - Grzegorz Biolik; Dariusz Gajniak; Maciej Kubicz; Damian Ziaja; Krzysztof Ziaja; Wacław Kuczmik (Mediators of Inflammation)
Knowledge about the influence of inflammation on platelet function and relocation of hemostatic balance to hypercoagulable state is still unclear. We compared two groups of patients who suffer from acute vs. chronic inflammatory process and additionally present high on-treatment platelet reactivity-dual platelet resistance. We did not found any differences in platelet aggregation between both investigated groups, but patients who suffer from chronic inflammation presented stronger relocation of the hemostatic balance to the hypercoagulability. A high concentration of prothrombin fragment F1+2 together with higher activity of von Willebrand factor in critical limb ischemia shows more exaggerated fibrinogen turnover although the blood concentration of this factor was in normal range. We concluded that high on-treatment platelet reactivity-dual platelet resistance and intensified inflammation are linked with elevated platelet and fibrinogen turnover to counteract proper hemostatic balance in favor of a prothrombotic state.